Controlling Nuclearity and Stereochemistry in Vanadyl(V) and Mixed Valent VIV/VV Complexes of Oxido‐Pincer Pyridine‐2, 6‐dimethanol Ligands. Issue 24 (22nd November 2018) - Nitsche, Sara; Schmitz, Simon; Stirnat, Kathrin; Sandleben, Aaron; Klein, Axel
Abstract : The coordination chemistry of three oxido‐pincer ligands 2, 6‐(HOC R 2 )2 (pyridine) (H2 L) based on 2, 6‐pyridinedimethanol [ R = H (H2 pydim), Me (H2 pydip), Ph (H2 pyphen)] towards vanadium(V) was explored. Reaction of NH4 VO3 with the protoligands H2 L gave the dinuclear complexes [(L)OV(μ‐O)VO(L)]. Mononuclear anionic species [VO2 (L)] –, which were isolated as alkaline metal salts were obtained from reactions of [VO(acac)2 ] (acac – = acetylacetonate) and H2 L under basic conditions and addition of HCl to these species allowed to isolate the unprecedented oxido chlorido complexes [VOCl(L)] for pydip and pyphen. Cyclic voltammograms of the dinuclear [V2 O3 (L)2 ] and mononuclear [VOCl(L)] complexes show reversible V V /V IV reduction waves, while corresponding waves of the anionic [VO2 (L)] – are completely irreversible. The mixed‐valent V IV /V V species [V2 O3 (L)2 ] · – were characterized by EPR and UV/Vis spectroelectrochemistry revealing a delocalized system with a 15 line EPR spectrum and an intervalence charge transfer (IVCT) band for the bulky pyphen ligand but localized radicals in case of the pydim and pydip derivatives (8 line EPR, no IVCT). DFT calculated structures of the three derivatives show an V–O–V arrangement for [V2 O3 (pyphen)2 ] · – of about 145° ideally suited for delocalization, whereas for [V2 O3 (pydip)2 ] · – an angle of 128° was found. Abstract :